2005
DOI: 10.1091/mbc.e05-03-0252
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-Va Regulates Exocytosis through the Submicromolar Ca2+-dependent Binding of Syntaxin-1A

Abstract: Myosin-Va is an actin-based processive motor that conveys intracellular cargoes. Synaptic vesicles are one of the most important cargoes for myosin-Va, but the role of mammalian myosin-Va in secretion is less clear than for its yeast homologue, Myo2p. In the current studies, we show that myosin-Va on synaptic vesicles interacts with syntaxin-1A, a t-SNARE involved in exocytosis, at or above 0.3 M Ca 2؉ . Interference with formation of the syntaxin-1A-myosin-Va complex reduces the exocytotic frequency in chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 52 publications
(135 reference statements)
7
78
0
1
Order By: Relevance
“…MyoVa, munc18, and syntaxin-1 may thus cooperate to mediate SG docking. This hypothesis is consistent with the reported interaction of MyoVa with syntaxin-1 (Watanabe et al, 2005), although this binding occurred at calcium concentrations unlikely to be found under resting conditions. Noteworthy, syntaxin-1 binding involves the neck region of MyoVa and not the motor head domain.…”
Section: Myova Mediates Secretory Granule Docking At the Plasma Membranesupporting
confidence: 92%
See 1 more Smart Citation
“…MyoVa, munc18, and syntaxin-1 may thus cooperate to mediate SG docking. This hypothesis is consistent with the reported interaction of MyoVa with syntaxin-1 (Watanabe et al, 2005), although this binding occurred at calcium concentrations unlikely to be found under resting conditions. Noteworthy, syntaxin-1 binding involves the neck region of MyoVa and not the motor head domain.…”
Section: Myova Mediates Secretory Granule Docking At the Plasma Membranesupporting
confidence: 92%
“…Another possibility is that MyoVa acts as a factor attaching SGs to the plasma membrane, in addition to, or instead of its role as a motor. This possibility was suggested by the observed interaction between MyoVa and syntaxin-1 (Watanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…It has been shown to be important in retaining these vesicular carriers (melanosomes, secretory granules) in the F-actin-rich cortex (Rudolf et al, 2003;Wu et al, 1998), and recently a role in fusion and exocytosis has also been reported via the interaction of myosin-Va with syntaxin-1A (Watanabe et al, 2005). Our data suggest that under basal conditions, microtubule-dependent transport of Na Intracellular transport is a complex process, driven by at least three types of motors: kinesins and dyneins involved in bidirectional transport along microtubules and myosins that move along actin filaments (King, 2000;Mermall et al, 1998;Woehlke and Schliwa, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include kinesin-1, which has been proposed to interact directly with amyloid precursor protein 137 ; however, data remain controversial 138 . Myosin Va interacts with syntaxin-1A in a Ca 2+ -dependent manner to regulate exocytosis 106 . In inner ear sensory cells, myosins Ia and VIIa interact with the integral membrane protein pleckstrin-homology domain retinal protein-1 (PHR1) 19 (panel b).…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…Actin is known to be crucial for synaptic-vesicle recycling 104 , and synaptic-vesicle movement at presynaptic terminals that are devoid of microtubules is dependent on myosin Va 105 . Myosin Va on synaptic vesicles directly interacts, in a Ca 2+ -dependent manner, with plasma membrane syntaxin-1a through its neck domain, and is thereby proposed to regulate stimulated exocytosis through the supply of readily releasable vesicles 106 . Nevertheless, the data linking myosin V with secretion still need to be confirmed in vivo.…”
Section: Outbound Trafficmentioning
confidence: 99%